Artistic Features of the Middle East Modern Tall Architecture. United Arab Emirates. Dubai - Andrei V. Korotich (Academia: Архитектура и строительство, 2018)
In article are considered some actual social aspects of artistic development of tall buildings architecture of Dubai (UAE); also showed the main problems and perspective directions/trends of their movement. Showed some new tall objects of Dubai which depend modern image of it's high-rise buildings architecture. Also considered some characteristic regional/national features of the modern tall imagine/symbolic architecture of the capital of emirate Dubai